Molecular characterization and gene expression of juvenile hormone binding protein in the bamboo borer, Omphisa fuscidentalis - Eakartit Ritdachyeng (2018)
Juvenile hormone (JH) plays an important role in many physiological processes in insect development, diapause and reproduction. An appropriate JH titer in hemolymph is essential for normal development in insects. Information concerning its carrier partner protein, juvenile hormone binding protein (JHBP), provides an alternative approach to understanding how JH regulates metamorphosis. In this study, we cloned and sequenced the Omphisa juvenile hormone binding protein (OfJHBP). The full-length OfJHBP cDNA sequence is comprised of 849 nucleotides with an open reading frame of 726. bp encoding 242 amino acids. The molecular mass of the protein was estimated to be 26.94. kDa. The deduced protein sequence of OfJHBP showed moderate homology with the lepidopteran, Heliothis virescens JHBP (52% amino acid identity) and lower homology with the Bombyx mori JHBP (45%) and the Manduca sexta JHBP (44%). The OfJHBP was expressed mainly in the fat body. OfJHBP transcripts in the fat body was moderately high during 3rd, 4th and 5th instars, then rapidly increased, reaching a peak during early diapause. The expression remained high in mid-diapause, then decreased in late-diapause until the pupal stage. Both juvenile hormone analog (JHA), methoprene, 20-hydroxyecdysone (20E) exhibited a similar stimulatory pattern in OfJHBP expression of diapausing larvae. OfJHBP mRNA levels gradually increased and showed a peak of gene expression on the penultimate, then declined to low levels in the pupal stage. For in vitro gene expression, both of JHA and 20E induced OfJHBP mRNA expression in fat body. Fat body maintenance in vitro in the presence of 0.1. μg/50. μl JHA induced OfJHBP mRNA expression to high levels within the first 30. min whereas 0.1. μg/50. μl 20E induced gene expression at 120. min. To study the synergistic effect of these two hormones, fat body was incubated in vitro with 0.1. μg/50. μl JHA or 0.1. μg/50. μl 20E or a combination of both hormone for 30. min. Induction of OfJHBP expression by JHA and 20E was significantly greater than that of either hormone alone. These results should contribute to our understanding of how JHBP and JH regulate the termination of larval diapause in the bamboo borer. © 2012 Elsevier Ltd.